Purification of recombinant fusion proteins carrying foreign antigens - Murugan, Sivasankar; Raj, Stephen M.L. (Asian Journal of Biological and Life Sciences, 2015)
Tuberculosis the well-known infectious disease in human beings is caused by Mycobacterium tuberculosis. The major antigens produced by M. tuberculosis during infection is CFP10, ESAT6, Ag85. Present study focuses on CFP10 which is a protective antigen that could induce immunity against tuberculosis. Being a lower molecular weight protein, CFP10 and IFN-γ is vulnerable for proteolytic degradation and consequently often failed to enhance the immunogenicity for longer time. Hence, it was fused with potyvirus coat protein to form virus like particles (VLPs) that could enhance the immunogenicity of the fusion partner. The potyvirus is a largest group of plant virus consist of coat protein (CP) synthesis from Johnsongrass mosaic virus (JGMV) expressed in bacteria or yeast resulted in the formation of potyvirus like particles (PVLPs). The aim of this study was to purify the recombinant fusion proteins (CFP10, CP:CFP10 and CP:IFN-γ) by chromatographic techniques and ultracentrifugation methods. Further, SDS-PAGE analysis was performed to confirm the purified fusion proteins to estimate the molecular weight. The purified protein was already immunized in mice to raise antibodies against CFP10 was determined by western blot. The purified recombinant fusion proteins CFP10, CP:CFP10 and CP:IFN- γ can be used as a diagnostic tool and development of vaccine against tuberculosis.
Keywords: Chromatography; Fusion proteins; Mycobacterium tuberculosis; Ultracentrifugation